31.A. Workshop: A holistic co-produced approach to self-management of diabetes across four European countries. (30th September 2020) - ,
Abstract: Diabetes is a long term non-communicable disease of major socioeconomic and public health significance. 60 million people live with diabetes in Europe and its prevalence is increasing across all ages, mostly associated with overweight and obesity, unhealthy diet and physical inactivity (WHO, 2018). Type 2 diabetes (T2D), accounting for 90% of those with this condition, is usually acquired in later life and can be successfully controlled through healthy lifestyle choices combined with appropriate medication when necessary. Self-management education programmes are viewed as a critical component in diabetes care, yet most of them are targeted only to at-risk groups, focussed on aspects of education and are not comprehensively evaluated for their added value to routine care. There is also lack of cross-national understanding of how such programmes can tackle common public health challenges experienced across Europe and improve quality of life of people with T2D. In this workshop, a holistic and co-produced approach to self-management of type 2 diabetes will be considered as was delivered by the Diabetes and WELLbeing (DWELL) 12-week psychoeducational programme across four European countries. DWELL was a four-year European project, funded by EU INTERREG 2Seas Mers Zeeën, involving healthcare providers and academics from UK, France, Netherlands and Belgium, to deliver a social innovation programme for people with type 2 diabetes. DWELL aimed to introduce a co-designed, co-produced programme in collaboration with T2D patients, focussing on empowerment of participants to access tailored support and take control of their condition by improving overall wellbeing. The cross-border collaboration also aimed to assist in developing a strategic approach and promote good practice and shared learning across the regions. The main new elements of DWELL were the combination of participant-driven design and delivery of the programme, shift of focus from medical condition to holistic care with emphasis on wellbeing and peer support, and a motivational approach to identify long-term lifestyle changes focussing on the person as a whole and not as a T2D patient. The workshop will provide the opportunity to consider the development and benefits of a novel approach to self-management of diabetes as well as lessons learnt by delivering a common programme in European countries with different approaches to diabetes care. The format of the workshop will be regular presentations followed by discussion with the audience. Presentations will introduce the DWELL programme and evaluation study protocol, interim quantitative findings of participant outcomes and qualitative findings in relation to participant experiences of the programme. Key messages: This workshop will deal with lessons learnt from a European project promoting a holistic and co-designed approach to self-management of type 2 diabetes. A complex interventions evaluation approach is important for comprehensive evidence of improvements in individual empowerment, healthy eating habits and control over condition.